Possible delayed diagnosis and treatment of metastatic differentiated thyroid cancer by adopting the 2015 ATA guidelines. Issue 3 (September 2018) - Albano, Domenico; Bertagna, Francesco; Bonacina, Mattia; Durmo, Rexhep; Cerudelli, Elisabetta; Gazzilli, Maria; Panarotto, Maria Beatrice; Formenti, Anna Maria; Mazziotti, Gherardo; Giustina, Andrea; Giubbini, Raffaele
Abstract : Objective: According to the 2015 American Thyroid Association (ATA) guidelines, thyroid ablation by iodine-131 (I-131) therapy is absolutely recommended only in patients with high-risk differentiated thyroid cancer (DTC). Often distant metastases are not recognized early and they can stay silent for long time. The aim of our study was to retrospectively analyze the prevalence of metastatic disease before and after I-131 and to evaluate the influence of the new ATA guidelines in the management of DTC. Methods: We retrospectively analyzed 140 patients showing distant metastases. All metastases were detected by whole-body scan after I-131 and confirmed by histology and/or other imaging modalities. Results: In 26/140 patients metastases were detected before I-131, while in 114/140 were discovered after I-131. Comparing patients with metastases detected before and after I-131, no differences were demonstrated considering age, sex, histotype, tumor size, multifocality of cancer and metastatic localization. Metastatic DTC discovered before radioiodine had higher thyroglobulin and received a higher radioiodine total activity and number of treatments. Considering patients with distant metastases, according to the 2015 ATA guidelines, 38 patients would have been categorized as high risk, 22 as low risk and 80 as intermediate risk. Among intermediate-risk patients, only in 25 cases (31%) I-131 treatment would have been appropriate according to 2015 ATA recommendations; in the remaining 56 cases (69%), I-131 would not have been recommended. Conclusions: According to the 2015 ATA guidelines, most of metastatic patients would not have been treated after surgery, with the risk of late diagnosis and delayed treatment.